Guarantees of the Right to Defense in Algerian Legislation - Dalila, Djelaila (Journal of Ecohumanism, 2025)
The accused enjoys a number of guarantees during the trial process. Some of these guarantees relate to the authority hearing the case, which must be independent and impartial. Others pertain to the fundamental principles of criminal procedure, such as the principle of legality, the prohibition of retroactive application of criminal law, and the principle of non bis in idem (not being tried for the same offense twice). Additional guarantees concern the procedural framework of the trial, including the principle of publicity, the requirement to document proceedings, adherence to procedural limits, and the presence of the accused during trial. There are also specific guarantees tied to the right of defense. These include the right of the accused to equal treatment in criminal proceedings by the competent authority, and the right to enjoy the same procedural protections as the opposing party. The accused must be informed of the charges against him and their content, and he has the right to consult with a lawyer and an interpreter if he does not speak or understand the language of the court. Moreover, the accused has the right to hear and cross-examine witnesses, and cannot be forced to testify against himself.